2016
DOI: 10.1371/journal.pone.0148952
|View full text |Cite
|
Sign up to set email alerts
|

Lower Neighborhood Socioeconomic Status Associated with Reduced Diversity of the Colonic Microbiota in Healthy Adults

Abstract: In the United States, there are persistent and widening socioeconomic gaps in morbidity and mortality from chronic diseases. Although most disparities research focuses on person-level socioeconomic-status, mounting evidence suggest that chronic diseases also pattern by the demographic characteristics of neighborhoods. Yet the biological mechanisms underlying these associations are poorly understood. There is increasing recognition that chronic diseases share common pathogenic features, some of which involve al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 68 publications
12
107
3
Order By: Relevance
“…The homogenous, quite small study population may influence our results. Ethnicity and socio‐economic status are known to affect the composition of gut and vaginal microbiota, but similar data are not available for skin microbiome studies . The study period was limited, so we decided to accept to the study four acne patients who had used oral tetracyclines, clindamycin‐benzoyl peroxide or adapalene locally for less than 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenous, quite small study population may influence our results. Ethnicity and socio‐economic status are known to affect the composition of gut and vaginal microbiota, but similar data are not available for skin microbiome studies . The study period was limited, so we decided to accept to the study four acne patients who had used oral tetracyclines, clindamycin‐benzoyl peroxide or adapalene locally for less than 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Western diets, and diets in Western and non‐Western lower socio‐economic populations, are both associated with a more inflammatory microbiota phenotype 56 . ‐ 58 …”
Section: What Causes Microbiota Differences?mentioning
confidence: 99%
“…Evidence shows that the healthier background diets of affluent families would help buffer the effects of Astrofood; for example, several studies have shown that tissue levels of phytochemicals and antioxidants-the sort that would buffer the effects of inflammation and metabolic dysregulation-are higher in association with individual and neighborhood SES advantage [172][173][174][175][176][177][178]. Research has shown that neighborhood disadvantage is associated with lower diversity of the intestinal microbiome; the gut microbial ecology coincident with deprivation (mostly through ultra-processed dietary patterns) may play important roles in metabolic disturbances [179].…”
Section: Disadvantage Compoundedmentioning
confidence: 99%